(x的平方-1分之6)-1=x-1分之3
来源:学生作业帮助网 编辑:作业帮 时间:2024/11/28 20:30:53
x){;7?SiGۓftV6IE*/ //yo=\3}8#]CMJ[c ȄHŵAP19PB.@
+t|y&p@
4]tȓO't\4YKӾ:n{1MVlx{)sWt=
lz*@a
(x的平方-1分之6)-1=x-1分之3
(x的平方-1分之6)-1=x-1分之3
(x的平方-1分之6)-1=x-1分之3
(x的平方-1分之6)-1=x-1分之3
解,得:
6/(x^2-1)-1==3/(x-1)
6-x^2+1==3(x+1)
-x^2+7==3x+3
-x^2-3x+4==0
x^2+3x-4==0
(x-1)(+4)==0
x1==1 (此解不合题意,去掉)
或 x2==-4
所以方程的解是:
x==-4
x的平方+x分之7-x的平方-1分之6+x的平方-x分之3=0
x分之3+x-1分之6=x的平方-x分之7
(x的平方+x分之7)+(x的平方-x分之1)=x的平方-1分之6 (2x-2分之5x+1)+2分之1=3x-3分之4x+10(x+2分之x-1)-(x的平方-4分之x-1)=1(-2-x分之3)在线等
(X-3分之X)-1=X的平方-3X分之6
(x²+x分之1)+(x的平方-x分之3)=(x²-1分之6)
x分之x+3=3分之1 a-b分之1-a+b分之1+a的平方+b的平方分之2b x-3分之x (-x的平方-3x分之x+6)+x分之1
x-3分之x-x的平方-3x分之x+6+x分之1
解方程:(1)x的平方+x-2分之3=x-1分之x - x+2分之x解方程:(1)x的平方+x-2分之3=x-1分之x - x+2分之x (2)x的平方-x-6分之5 - x的平方-4分之6 =x的平方-5x+6分之4 (3)x+5分之一 + x+8分之一 = x+6分之
(x-2)分之x+(4-x的平方)分之(x+6)=[x+2)分之(2x)]+1(1-9x的平方)分之3x=二分之一-(6x-2)分之x
x平方+x分之7 + 1-x平方分之6=x-x平方分之1
x的平方+x分之7+x的平方-x分之1=x的平方-1分之6
x的平方+x分之7+x的平方-x分之1=x的平方-1分之6
x的平方+x分之7+x的平方-x分之1=x的平方-1分之6
1、(a+b)的平方分之1,-a+b分之1,a的平方-b的平方分之1,通分2、x的平方+2x分之x ,x的平方-4分之1的最简公分母3、x的平方+x-2分之2,x的平方-x-6分之1 通分4.x-1分之1 + x+1分之1=?
解方程:x平方+x分之7+x平方-x分之3=x平方-1分之6
2x-3分之x+()=2x-3分之1x-2y分之x的平方-()=x-2y分之4y的平方
x的平方-x分之x+5+1-x分之6=x分之3 解分式方程,
(2) x-3分之5-x的平方-9分之x-2+2x-6分之x-1